Design of pitch angle controller for wind turbine based on pi neurofuzzy model - Ammar A. Aldair; Mofeed T. Rashid; Ali F. Halihal; Mastaneh Mokayef (Institute of Advanced Engineering and Science, 2019)
Aerodynamic torque of wind turbine is adjusted by controlling the pitch angle of the blades of the turbine when the wind speed is higher than rated wind speed. So that, in the recent research in this field, the pitch angle controller becomes dominated controller type for extracting the electrical power from the wind energy. Three types of the pitch angle control systems are designed to construct the speed controller: conventional PI controller, Neurofuzzy controller and modified PI-Neurofuzzy controller. The results are shown that the modified PI-Neurofuzzy controller is more efficient than the others because the rotation speed of generator is kept almost constant. It means that the generated output power has remained constant at maximum power limited even the wind speed rises up the rated wind speed.